2012
DOI: 10.4103/0973-1482.103517
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile in oral cancer and leukoplakia: Correlation with tobacco abuse and histological grading

Abstract: There may be an inverse relationship between serum lipid profile and OC. No significant reduction in lipid profile was observed in the OLP group. This may indicate that hypolipidemia is a late change occurring during carcinogenesis or is an effect rather than the cause of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2106
2106

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…6 However in contrary to afore mentioned statement, we observed the mean serum lipid parameters TC, TG, HDL, LDL, VLDL, showed no significant p value according to degree of differentiation. Similar findings were also obtained in the studies by Jyothi Chawda et al, 7 Kumar P et al 8 and Anuradha et al 9 In the present study, the serum lipid profile parameters like TC, HDL and VLDL showed lower values in PMD and OC groups when compared to control group. TG and LDL showed no significant changes.…”
Section: Discussionsupporting
confidence: 80%
“…6 However in contrary to afore mentioned statement, we observed the mean serum lipid parameters TC, TG, HDL, LDL, VLDL, showed no significant p value according to degree of differentiation. Similar findings were also obtained in the studies by Jyothi Chawda et al, 7 Kumar P et al 8 and Anuradha et al 9 In the present study, the serum lipid profile parameters like TC, HDL and VLDL showed lower values in PMD and OC groups when compared to control group. TG and LDL showed no significant changes.…”
Section: Discussionsupporting
confidence: 80%
“…Oral cancer is the leading cause of morbidity and mortality in India and is most commonly preceded by clinically definable premalignant lesions and conditions (2). OSMF is regarded as a precancerous condition and shows a significant tendency to develop cancer (3).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is also equally important to detect and control the premalignant lesions and conditions (3). Early detection of these conditions can dramatically improve the treatment outcome and prognosis in such patients (2). …”
Section: Introductionmentioning
confidence: 99%
“…Kumar Priya et. al., (2012) 17 have also described the behaviour of Serum lipid profile in oral cancer and leukoplakia and also established the linkage with tobacco abuse and histological grading. In recent past year, Mirza Arsalan Baig et al 2014 18 studied deals to evaluate lipid profile in oral cancer patients and correlate their lipid profile with carcinogenesis.…”
Section: -24mentioning
confidence: 98%
“…(iii) plasma lipid profile levels may be a useful indicator reflecting initial changes occurring in precancerous and neoplastic conditions. [15][16][17][18][19] Realizing the above perspective kept in mind and in view of very limited concise studies on the altered level of various lipid profile parameters, especially in different stages of OC patients of the public health interest, therefore, the main objective has been planned in the present course of the investigation to assess the altering in several serum lipid profile parameters for oral cancer patients with the non-oral cancer cases.…”
Section: International Journal Of Community Health and Medical Researmentioning
confidence: 99%